2014
DOI: 10.1002/ps.3702
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐treatment autodissemination station with enhanced transfer of an insect growth regulator to mosquito oviposition sites

Abstract: The oil and pyriproxyfen powder dual-treatment station enhanced autodissemination efficacy by increasing toxicant attachment and retention on contaminated females. The autodissemination station offers a targeted, less environmentally damaging approach to manage cryptic container species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…albopictus to deliver pyriproxyfen to larval habitats [12,14,30]. Attracted to the station by an oak infusion, the mosquito enters the station but is unable to reach the water and oviposit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…albopictus to deliver pyriproxyfen to larval habitats [12,14,30]. Attracted to the station by an oak infusion, the mosquito enters the station but is unable to reach the water and oviposit.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of pyriproxyfen on non-targets is minimal as dissemination is tightly targeted to small, scattered, container habitats. Additionally, the amount carried by females is minuscule which further reduces insecticide load in the environment [14]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Koama et al showed that a single exposure to pyriproxyfen treated netting reduced the number of eggs laid by >75% over three gonotrophic cycles when the first blood-meal was shortly after exposure (Koama et al, 2015). It has been shown that pyriproxyfen is a potent inhibitor of pupal eclosion at very low concentrations and that adult mosquitoes can transfer pyriproxyfen to larval waters during oviposition (Mbare et al, 2014;Wang et al, 2014;Lwetoijera et al, 2014b). The impact of so-called autodissemination will depend on the dosage of pyriproxyfen remaining on tarsi by the time of oviposition and the volume of water in breeding sites.…”
Section: Discussionmentioning
confidence: 96%